2020
DOI: 10.1136/lupus-2020-000419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the LFA-REAL clinician-reported outcome (ClinRO) and patient-reported outcome (PRO): data from the Peruvian Almenara Lupus Cohort

Abstract: ObjectiveThe Lupus Foundation of America Rapid Evaluation of Activity in Lupus (LFA-REAL) clinician-reported outcome (ClinRO) and the LFA-REAL patient-reported outcome (PRO) were developed in order to capture manifestations of SLE from the perspective of both the clinician and the patient. The aim of this study is to compare the LFA-REAL ClinRO and PRO with other lupus disease activity measures.MethodsA cross-sectional analysis of patients from a single-centre cohort was performed using Spearman’s correlation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…This study confirms the experience of many rheumatologists in practice: severe patient-reported symptoms do not invariably indicate active inflammation and, furthermore, often do no correlate with physician indices of disease activity. 17,33,34 These findings are consistent with our previous studies which showed that patients, who according to their rheumatologist had Type 2 SLE activity without Type 1 activity, frequently reported a recent disease flare as well as moderate-severe symptoms of dry eyes, oral/nasal ulcers, shortness of breath, and stiff and swollen joints. 17 Previous studies have shown discordance in how patients and their rheumatologists score disease activity, with many patients reporting higher levels of activity than their rheumatologists report.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms the experience of many rheumatologists in practice: severe patient-reported symptoms do not invariably indicate active inflammation and, furthermore, often do no correlate with physician indices of disease activity. 17,33,34 These findings are consistent with our previous studies which showed that patients, who according to their rheumatologist had Type 2 SLE activity without Type 1 activity, frequently reported a recent disease flare as well as moderate-severe symptoms of dry eyes, oral/nasal ulcers, shortness of breath, and stiff and swollen joints. 17 Previous studies have shown discordance in how patients and their rheumatologists score disease activity, with many patients reporting higher levels of activity than their rheumatologists report.…”
Section: Discussionsupporting
confidence: 91%
“…The LFA-REAL ClinRO tries to improve the disadvantage of previous scores by trying to remain simple, like the SLEDAI or the PGA; it includes 14 domains and 1 VAS from 0 to 100 for each domain, with a score ranging from 0 to 1400, but also with the possibility of including all possible manifestations. It has been shown to correlate with the SLEDAI-2K and the PGA in several cohorts as well as in a clinical trial, 11,14,[27][28][29] but this is the first study evaluating its predictive value on damage accrual.…”
Section: Discussionmentioning
confidence: 99%
“…The first one includes only individual manifestations and does not include the global measurement of mucocutaneous and musculoskeletal involvement but rather their subdomains; it ranges from 0 to 1400 (the sum of 14 VAS). The alternative option includes only the global domains and not the individual manifestations except for others in which 3 are allowed; this gives a range of 0 to 1100 (the sum of 11 VAS) 11,14 . To be recorded in the LFA-REAL ClinRO, the manifestation should be related to SLE activity, and not to damage or comorbidities; as described in the original tool, the clinician does the attribution of all manifestations; in the present study, one of our previously trained investigators applied it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation